NILAI-NILAI TRADISIONAL TOLAK BALA DI DESA BETUNG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Gustiranto "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study analyzes the traditional values starting reinforcements in the village of Betung District of Pangkalan Kuras, starting reinforcements ritual is a series of activities to prevent and avoid from a wide variety of reinforcements as well as disturbances of supernatural beings such as ghosts, jinn, okuan and so forth. Basically, this ritual has become a tradition that can not be abandoned by society Petalangan village of Betung, because of the tradition of ritual starting reinforcements this is a promise that has been made from a common ancestor that were preserved by the community Petalangan village of Betung is a promise to pay the debt by offering animal heads like goats or buffalo. The purpose of this study was to gain insights into how the process of starting reinforcements ritual performance in terms of practice and implementation objectives. While the benefits of research in the academic field as a donation notion, especially sociology to know the ritual starting reinforcements from different sides. The method used in this research is qualitative. Data collection techniques are observation, interviews, and documentation. Analysis of the data by descriptive analytic approach, which seeks to portray and interpret objects in accordance with what it is. From the research results in the field indicate that the public Petalangan village of Betung until now still trust and carry out the tradition of ritual starting reinforcements every year at the beginning of the month, or more precisely on the 15th, and the tradition of ritual starting reinforcements should not be abandoned by society Petalanagan village of Betung because starting reinforcements ritual tradition is an agreement that has existed since the time of the ancestors is the agreement to repay the debt by offering a goat or buffalo head, and if the debt is not paid, would be many plagues that will befall the community Petalangan Betung Village. Hence the tradition of starting reinforcements ritual is not separated from public life Petalangan Betung Village Pelalawan District of Pangkalan Kuras.Keywords: Reject, Bala, Values, Traditional.